End-of-Life Care Attitudes, Values, and Practices Among Health Care Workers. (March 2014) - Goel, Ashish; Chhabra, Gaurav; Weijma, Robyn; Solari, Marla; Thornton, Sarah; Achondo, Bernardita; Pruthi, Sonal; Gupta, Vineet; Kalantri, S. P.; Ramavat, Anurag S.; Kalra, O. P.
Introduction: This study aims to ascertain attitudes of health care workers on end-of-life care (EOLC) issues and to highlight the disparity that exists in countries with different backgrounds. Methods: It is a cross-sectional questionnaire survey across heterogeneous health care providers in India, Chile, the United Kingdom, and the Netherlands using an indigenously prepared questionnaire considering regional variations, covering different areas of EOLC. Results: Of the 109 participants, 68 (62.4%) felt that cardiopulmonary resuscitation should be done selectively, 25 (22.9%) had come in contact with at least 1 patient who had asked them to hasten death, and 36 (33%) felt that training was insufficient to prepare them for skills in issues of EOLC. Conclusion: To avoid cumbersome through well-meant interventions, it is important that the caregiving team is aware of the patient's own wishes with respect to EOLC issues.